An annotated catalog of the type material of Mecoptera deposited in the Florida State Collection of Arthropods in Gainesville, Florida, USA - Keller, Oliver; Somma, Louis A. (Zootaxa, 2023)
The Florida State Collection of Arthropods (FSCA) is one of the largest and most valuable insect collections in the United States with more than twelve million curated specimens. The order Mecoptera currently comprises over 800 extant described species in nine extant families. The FSCA houses type material in the families Bittacidae, Panorpidae, and Panorpodidae. This catalog documents the FSCA type material for 23 species in five genera in Mecoptera.